Survival Benefit of Metformin Use for Pancreatic Cancer Patients Who Underwent Pancreatectomy: Results From a Meta-Analysis - Zhang, Junqiang; Ma, Jichun; Guo, Lingyun; Yuan, Bo; Jiao, Zuoyi; Li, Yumin (Frontiers in Medicine, 2020)
Objective The aim of this meta-analysis was to evaluate the survival benefit of metformin for pancreatic cancer (PC) underwent pancreatectomy. Methods PubMed, EMBASE and the Cochrane Library databases were searched to identify studies relevant to survival benefit of metformin for patients with pancreatic cancer underwent pancreatectomy until June 30, 2019. Two reviewers independently extracted relevant data from included studies. HR and its 95% confidence interval(CI) were pooled by being performed STATA 12.0 software. Results All of 12 studies consisting of 35346 pancreatic cancer patients were eligible and included in this meta-analysis. The result of meta-analysis under a random-model showed that there are significant differences in overall survival(HR=0.85, 95%CI: 0.77-0.94, P=0.002) between PC patients treated with metformin underwent pancreatectomy and PC patients treated without metformin underwent pancreatectomy. Subgroup analyses by ethnicity showed a significantly reduced risk of death for metformin users compared with non-users in Caucasians (HR=0.903, 95% CI=0.825-0.940, P=0.008) and Asian (HR=0.691, 95% CI=0.588-0.813, P=0.001). It was also showed a remarkable reduction of mortality risk in patients at stage I-II treated with metformin (HR=0.762, 95% CI=0.677-0.858, P=0.0001) as well as the group at stage I-IV(HR=0.884, 95% CI=0.791-0.988, P=0.030). Conclusions Metformin use is associated with survival benefit for pancreatic cancer patients underwent pancreatectomy, suggesting a potentially available option for the treatment.